Association between knowledge, attitude and preventive practices on malaria among pregnant women with and without malaria attending ante-natal care in Zamfara state, Nigeria - Hadiza, Kallamu; Abdul Rahman, Hejar; Kadir @ Shahar, Hayati; U. G., Ismaila (Community Health Society Malaysia, 2015)
Background: Malaria during pregnancy is a major public health problem, with substantial risks for the mother and her foetus. The aim of this study was to assess the knowledge, attitude and preventive practices of malaria among pregnant women diagnosed with and without malaria attending ante-natal care in Zamfara State, Nigeria.